International Environmental Agreements: Incentive Contracts with Multilateral Externalities - Carsten Helm; Franz Wirl (University of Oldenburg, Department of Economics, 2011)
We consider how one party can induce another party to join an international emission compact given private information. Due to multilateral externalities the principal uses her own emissions besides subsidies to incentivize the agent. This leads to a number of non-standard features: Optimal contracts can include a boundary part, which is not a copy of the no contract outcome. Compared to this, a contract can increase emissions of the principal for inefficient types. Subsidies can be constant or even decreasing and turn negative, i.e., the agent reduces emissions and pays the principal.
Keywords: D82; Q54; H87; 330; private information; multilateral externalities; mechanism design; restricted contracts; environmental agreements